Вы находитесь на странице: 1из 0

.. 3. .

3.3.
. x (. 3.27)
:
i( x )
:
- Du = R Dx i ( x ) + L Dx
(3.50)
t
(u ( x ) + Du )
:
- Di = (u ( x ) + Du ) G Dx + C Dx
(3.51)
t
x0 (3.51) :
u ( x )
- Di = u ( x ) G Dx + C Dx
(3.52)
t
(3.50) (3.52) .
x x0:
u
i
= R i + L
x
t
(3.54)
i
u
= G u + C
x
t
.

,
. ,

.

. 3.27.

. .
-, .
.
-, .
.
.
(3.54) u U& ,
i I& . ,
j. :
dU&
&
- dx = ( R + jwL ) I
(3.55)
&
d
I
= (G + jwC ) U&
dx
.
. 3.28 . (3.55).
1 13

.. 3. .

I&0

U& 0

I&

U&

I&l

U& l

. 3.28. , (3.55)

I& .
x I& x:
d 2U&
dI&
- 2 = ( R + jw L )
= (R + jwL ) (G + jwC ) U&
(3.56)
dx
dx
g = (R + jwL ) (G + jwC ) , (3.56) :
d 2U&
- 2 = g 2 U&
(3.57)
dx
(3.57) :
U& = A exp(g x ) + B exp (- g x ) .
(3.58)
(3.69) :
G + jwC
(3.59)
I& = ( A exp (g x ) - B exp(- g x ))
R + jwL
R + jw L
, ,
G + jwC
.
Zv (3.59) :
I& Z v = - A exp(g x ) + B exp(- g x )
(3.60)
(3.58) (3.60) - A B.
, . , I&0
U& x = 0. (3.58) (3.60) :

Z v =

U& 0 = A + B
&
I 0 Z v = - A + B
(3.61) A B, :
U& - I& Z
U& + I& Z
A= 0 0 v
B= 0 0 v
2
2
A B (3.58) (3.60), :
& U& 0 - I&0 Z v
U& 0 + I&0 Z v
exp
(
g
)
U
=

x
+
exp(g x )

2
2

&
&
&
&
I& Z = - U 0 - I 0 Z v exp(- g x ) + U 0 + I 0 Z v exp (g x )
v

2
2
, :

(3.61)

(3.62)

(3.63)

2 13

.. 3. .

U& = U& 0 ch(g x ) - I&0 Z v sh(g x )

(3.64)
& &
U& 0
I
I
ch
x
(
g
)
=

sh(g x )
0

Zv

exp (g x ) + exp(- g x )

- ,
ch(g x ) =
2
exp(g x ) - exp(- g x )
sh(g x ) =
- .
2
(3.63) U& I& , U& 0 I&0 . (y = l, x = l), . (3.64)
:
U& l = U& 0 ch(g l ) - I&0 Z v sh(g l )

(3.65)
& &
U& 0
I
I
ch
l
(
g
)
=

sh (g l )
0
l
Zv

(3.64) .
, U& l I&l Zl:
U&
(3.66)
Zl = & l
Il
, :
U& l Z l - Z v
(3.67)
=
pl =
U& l Z l + Z v
:
&
&
& &
& = U l + I l Z v [exp(g x ) + p exp(- g x )]
U
U
U
=
+
l

(3.68)

& + I& Z
U
l
l
v
I& = I& + I& =
[exp(g x ) - pl exp(- g x )]

2 Zv
(3.68) , : , , , . Zv .
.
, Z 0 = Z l = Z v , (3.64) :
U& = U& 0 exp(- g x )
(3.69)
& &
I = I 0 exp(- g x )

3 13

.. 3. .

3.4. .
3.4.1. .
3.3 , - g . .
g - ,
. :
g = (R + jwL ) (G + jwC ) .
(3.70)
:
g = a + jb ,
(3.70)

[1/] , [1/] .

, : a = Da Dl , /.

1 U& I& e = 2.73 . /. : 1 = 8.68 .


, :
U l = U 0 exp(- al )
, :

U l = U 0 10

-al
20

, : b = Dj Dl , /.

vp :
w
vp = .
(3.71)
b
, , 2:
2p v p
=
,
(3.72)
l=
b
f
f .

Zv - , .
:
R + jw L
(3.73)
Z v = Z v exp( j j v ) =
G + jwC
4 13

.. 3. .

.
, , , Zv, vp .

3.4.2. .
3.4.1 , , .
.
,
.
w 0
R0 >> wL , G0 >> wC . , R = R0 , ,
G = G0 . :

a @ R0G0 = const (w )
R0
Zv @
G0

wC
1 - j
2G0

b@

wC
2

R0
G0

R0
Zv @
= const (w )
G0

vp =

w 2 G0
@
= const (w )
b C R0

wC
wC
jv @ -arctg
2G0
2G0

(3.74)


, R = R0 > wL ,
. ,
G < wC . :
R0wC
R0wC
2w
w
a@
b@
vp = @
2
2
b
R0 C
(3.75)
R0
R0
wL
p wL
Zv @
jv @ - +
Zv @
1+ j
jwC
wC
R0
4 2 R0

R > R0 , wL > R , wC > G .

w
1
@
= const (w )
b
LC
(3.76)
L
L
R
R
Zv @
Zv @
= const (w ) jv = 1- j
C
C
2wL
2wL
. 3.29 (
0.5
0.9 ). ,
(3.74), w (3.75). , :
R C G L
a=
+
= am + ad
(3.77)
2 L 2 C
a R G. R w (3.12), G - w (3.49). , a@

R C G L
+
2 L 2 C

b @ w LC

vp =

5 13

.. 3. .

, a m > a d a w .
- ad a m < a d a w.

R0wC
2
R0 G0

R C G L
+
2 L 2 C

. 3.29. .

. 3.39 (
0.5 0.9
). , w (3.74),
w (3.75), w (3.76).
, /

w LC

wC R0
2 G0

R0wC
2

f,

. 3.30. .

. 3.31 . ,
w (3.75), -
L C (3.76). .
, - .
: |Zv| . 3.31 :
G0. |Zv| .
6 13

.. 3. .
Z v ,

Zv

R0
G0

R0
w

f,
v,

wC
2G0

R
2wL

p wL
+
4 2 R0

f,

. 3.31. .

. 3.32 . , w
(3.75), 1 LC (3.76).

1
LC

2 G0

C R0

2w
R0 C

. 3.32. .

.
( )
, vp . .
7 13

.. 3. .

3.5.

a - , , (
. a , a
(3.77). a m >> a d , L = L , :

a = am =
Z v =

R C
R
,
=
2 L 2 Z v

(3.78)

L
- .
C

3.5.1.
. , s m. :
1 1
1
1 rb
w m m0
1 + ,
(3.79)
+ =

R=
2p rb ra
2psq ra rb
2s

L = L =

m m0
r
ln b ;
2p
ra

(3.80)

2pee 0
.
(3.81)
rb
ln
ra
, :
r
1+ b
ra 1
w m ee 0
.
(3.82)
a = am =

rb 2rb
2m s
ln
ra
(3.140) , (
rb) a rb / ra, am ra 0 ra rb. ,
rb / ra, am . rb / ra :
1+ x
A( x ) =
.
(3.83)
ln x
A, :
1
ln x - (1 + x )
dA( x )
x.
=
(3.84)
2
dx
ln x
C=

, :
1
ln x = 1 +
.
x

(3.85)

(3.85) (. 3.33). x = rb / ra = 3.6.


8 13

.. 3. .

() ( ) rb / ra 9.4 / 2.6 = 3.61.


, A(x) .
, x = 3.6
,
().

x = rb ra
rb / ra = 4.6 / 1.2 = 3.83. , ,
1

1+
75 .
x

( ) ln x

x = 3.6
, (
), Zv
x = rb ra

rb / ra.
. 3.33. .

, ,
. , ,
x = rb / ra = 3.9.
A( x )

3.5.2.
:
2
ra
1+ 2
a w m m0 ,
(3.86)
R=
p ra
2s
m m
a - ra
L = L = 0 ln
;
(3.87)
ra
p
p e e0
.
(3.88)
=
a - ra
ln
ra
:
a - ra m m 0
L 1
Z v =
.
(3.89)
= ln
C p
ra
e e0
, :

9 13

.. 3. .
2

ra

1+ 2

a 1 w m e e 0

a = am =
(3.90)
2a
2m s
a

ln - 1
ra

a / ra :
2

x 1 + 2
x
A( x ) =
.
(3.91)
ln ( x - 1)
A,
A( x )
:
2

x 1 + 2
2
x

ln ( x - 1)1 - 2 -
dA( x )
x
x -1

=
2
dx
ln ( x - 1)

a
ra

x = a ra
2

x 1 + 2
x
(x - 1) 1 - 22
x

(3.92)
,
:

2
x 1 + 2
x

ln ( x - 1) =

(x - 1) 1 - 22
x

(3.93)

(3.93) .
. 3.34 A
x = a ra
. 3.34. .
(3.93).
x = a / ra = 5.2.
. 3.51 , A ,
, ,
. a = 4.2 , ra = 0.6 ,
a / ra = 7. ra = 0.8 . 4.5% 81.2%.
ln (x - 1)

x = 5.2

3.6.
, :
U&
(3.94)
Z = 0
I&
0

10 13

.. 3. .

(3.65) :
Zl
ch(g l ) + sh(g l )
Zv
,
Z = Z v
Zl
ch(g l ) +
sh(g l )
Zv
Z = U& I& - .
l

(3.95)

:
1. .

, Zl = Zv. Z = Z l = Z v
2. .
l 0 , g l 0 , sh(g l ) 0 , ch(g l ) 1 . Z Z l .
3. .
exp(g l )
exp(g l )
l , g l , sh(g l )
, ch(g l )
.
2
2
Z Z v . , , .
4. .
sh(g l )
= Z v th(g l ) .
Zl = 0, Ul = 0 Z = Z v
ch(g l )
5. .
ch(g l )
= Z v cth(g l ) .
Z l , Il = 0 Z = Z v
sh(g l )

3.7.


.
&
U& 0
Ul
:
P
a = 10 lg 0 ,
Pl
(3.96)
. 3.35. .
1 P0
a = ln ,
2 Pl
:
P&l = U& l I&l .
(3.97)
I&0

I&l

, P0, , (3.96), , .

3.7.1.
,
Z0 = Zv = Zl. P0 :
P&0 = U& 0 I&0 .
(3.98)
:
U
U2
E2
E
Z = Z v , I 0 = 0 U 0 = , P0 = U 0 I 0 = 0 =
Zv
2
Zv 4 Zv
11 13

.. 3. .

E2
(3.99)
exp (- 2al )
4 Zv
(3.96), :
P 1
1
(3.100)
a = ln 0 = ln (exp (- 2al )) = a l .
2
Pl 2
( ). a ( ). a f (. 3.36).
Pl = U l I l = U 0 I 0 exp(- 2al ) =

a,

a,

l2 > l1

f2 > f1

f2

l2
l1

f1

l,

f,

. 3.36. .

3.6.2.
, : Z0 Zv,
Zl Zv. , - Z0 Zl . , Zv , Z0 Zl ,
. Zv , .
Z0
P0 , Z0 , Z0 (. 3.37).
Z0
E
E
E
E2
(3.101)
P0 =
=
2 2 Z0
4 Z0
. 3.37. P0
, Pl
.
, :
E 2 Z v 1 - pl2 exp (- 2 gl )
(3.102)
Pl = U& l I&l =
(Z v + Z 0 )2 [1 - p0 pl exp (- 2 gl )]2

:
1
1
a p = a l - ln 1 - p02 - ln 1 - pl2 + ln 1 - p0 pl exp (- 2gl )
2
2

(3.103)

12 13

.. 3. .

, ac = a l ; ,
:
1
a 0 = - ln 1 - p02 ,
(3.104)
2
1
a l = - ln 1 - pl2 ;
(3.105)
2
, , :
a = ln 1 - p0 pl exp (- 2gl ) .

(3.106)
a,

l = const

a
a

al
a0

2l

. 3.38. 2bl.

3.7.3.

, :
Z0 Zv, Zl Zv.
P0 ,
Z0 ,
Zl (. 3.39).

E 2 Zl
(3.107)
P0 =
(Z 0 + Z l )2
Pl . (3.102) . :
0,
a = a + a l + a + a
(3.108)
. 3.49. P0
.

0 =
a

4Z 0 Z l
1
1
= a 0 + a
ln 1 - p 02 + ln
2
2 (Z 0 + Z l )2

13 13